Update on premature physeal closure. Diagnosis and treatment. Issue 1 (16th February 2021) - de Pablos, Julio; Arenas-Miquelez, Antonio; Arbeloa-Gutierrez, Lucas
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: Premature Physeal Closure (PPC) is the most common consequence of a mostly posttraumatic, physeal injury. They are of utmost importance because they can significantly alter physeal function and lead to disorders such as limb length discrepancies and angular deformities. Recent findings: The type of physeal fracture has not demonstrated a solid predictive value in the formation of PPC, especially in the knee where almost any type of fracture can produce it. The detection of physeal damage with imaging tests (simple radiology and MRI) is very accurate; however, their predictive capacity to foretell which injury will generate a physeal bridge is still poor. For this reason, it is not advisable to make surgical decisions at the first medical assessment. Direct surgical management of PPC's (resection-interposition technique) has generally shown high unpredictability. Nevertheless, the latest interposition materials (chondrocytes and mesenchymal stem cells) showed promising results. Summary: PPC is an often devastating consequence of physeal injury and as such deserves further research. To date little is known about etiopathogenesis, risk factors and natural history among other aspects. Until direct surgery offers more consistent results, acute osteotomies and bone distraction for progressive correction continue to be the most widespread treatments for PPCs.